Higher Education, Vocational Training and Performance of Firms. (February 2021) - Sangita, Seema
This article contributes to the debate on the efficacy of traditional forms of education versus vocational training. The effects of technical education (leading to an engineering degree or diploma) and vocational training in engineering on the performance of Indian firms are analysed using regression models based on the Cobb–Douglas production function, enhanced to incorporate education and training. Instrumental variable approach is used to establish the direction of causality. It is found that that when a larger share of workers in a particular sector has a college or university-level technical education or vocational education in technical fields, there is a positive impact on firm performance in those sectors. Further, higher education in a general field seems to consistently benefit the organised manufacturing sector, while some levels of school education appear to benefit the unorganised sectors. JEL codes: I-23; L-60; M-53